2010
DOI: 10.5666/kmj.2010.50.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Meromorphic Function that Shares One Small Function with its Differential Polynomial

Abstract: In this paper, we investigate the uniqueness problems of meromorphic functions that share a small function with its differential polynomials, and give a result which is related to a conjecture of R. Brück and improve the results of I. Lahiri and Q. C. Zhang.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In 1999, Yang [10] confirmed that the Conjecture is also true when f is replaced by f (k) (k ≥ 2) and f is of finite order. In recent years, many results have been published concerning the above conjecture, see [2,5,7,8,14,15,16,17,18] etc., and Zhang [17] was the first author who considers the case when f is a meromorphic function. We need the following definition.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Yang [10] confirmed that the Conjecture is also true when f is replaced by f (k) (k ≥ 2) and f is of finite order. In recent years, many results have been published concerning the above conjecture, see [2,5,7,8,14,15,16,17,18] etc., and Zhang [17] was the first author who considers the case when f is a meromorphic function. We need the following definition.…”
Section: Introductionmentioning
confidence: 99%
“…Since q 0j ≥ 1, it is clear from equation (4) Proof. The proof is similar to the proof of the Lemma 2.4 of ( [6]).…”
Section: Lemmasmentioning
confidence: 77%
“…As (f (k) ) m is simply a special differential monomial in f , it will be interesting to investigate whether Theorems D-H can be extended up to differential polynomial generated by f . In this direction recently Li and Yang [11] improved Theorem D in the following manner.…”
Section: Introduction Definitions and Resultsmentioning
confidence: 99%